Analisis Personal Branding Jeniffer Coppen sebagai Influencer dan Entrepreneur di Media Instagram - Afifah Rosanti; Fitrinanda An Nur (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The development of social media has changed the way public figures shape and manage their image. Before the digital era, their existence was limited to conventional media, but the presence of platforms such as Instagram provides a wider space to form a professional identity through personal branding. This research aims to analyze how Jennifer Coppen's personal branding as an Influencer and Entrepreneur is formed through Instagram posts based on Peter Montoya's Eight Laws of Personal Branding concept. This research uses a qualitative descriptive approach by analyzing the content of posts during the period July 2024 to June 2025. The results show that Jennifer consistently displays an image as an independent single mom, as well as an influencer who is active in product promotion and running a business. Instagram is used as the main space in displaying the balance between personal life and professional roles. Personal branding is an important strategy that not only expands her reach, but also opens up opportunities for cooperation and strengthens her commercial position as an influencer and entrepreneur and increases emotional connection with her followers.